On Time : from seasons to split seconds - Gloria Skurzynski (Washington, D.C. : National Geographic Society, 2000)
Examines the ways humans have measured time throughout history and discusses the various units that are used to keep track of it.
Keywords: Non Fiction -- Non Fiction